INDICENTAL ANATOMICAL VARIATION OF THE CELIAC TRUNK ORIGIN (Vietnam Journal of Community Medicine, 2026)
Background: The celiac axis (CA) typically originates from the abdominal aorta at the level of the first lumbar vertebra (L1). An origin from the thoracic aorta is an extremely rare anatomical variation. Identifying this variant is crucial for surgical planning and interventional radiology procedures.Case Report: A 62-year-old male patient underwent multi-detector computed tomography (MDCT) of the abdomen and pelvis for a left inguinal hernia. Imaging incidentally revealed the CA originating from the thoracic aorta, above the diaphragmatic aortic hiatus and approximately 13 mm higher than its typical position. There were no radiological signs of compression or clinical symptoms suggestive of mesenteric ischemia.Conclusion: High origin of the celiac axis is a rare variant and should be differentiated from median arcuate ligament syndrome. Multi-detector CT with 3D reconstruction provides an accurate description of vascular anatomy, playing a crucial role in diagnosis and surgical planning.
Keywords: Celiac axis, anatomical variant, thoracic aorta, median arcuate ligament, multi-detector computed tomography (MDCT).